WISATAWAN DALAM PERSEPSI TERHADAP DAYA TARIK WISATA HERITAGE DE TJOLOMADOE - Erlina Daru Kuntari; Adesty Lasally (STIE Pariwisata API Yogyakarta, 2021)
This study aims to determine the perception of tourists on aspects of heritage tourism at De Tjolomadoe. The data collection method used is the distribution of online questionnaires. The analytical method used is descriptive, covering the characteristics of the respondents and the characteristics of the attractiveness of the De Tjolomadoe tourist attraction. The characteristics of the respondents in this study, namely the majority of male tourists; private employment; undergraduate education; and the population of Central Java. Meanwhile, the characteristics of tourist objects are: tourists consider ticket prices cheap; good image of tourist destinations; recommend De Tjolomadoe as a tourist destination; the majority of tourists who visit use private cars; tourists do not use lodging while visiting; visits are made from the family; Destination information is obtained through friends or relatives. Tourists are motivated to come because they have never been to a tourist location; tourists consider the architecture of the building to be the most attractive attraction. The analysis of heritage aspects includes aspects: rarity, history, superlativity, plurality, influence and aesthetics. De Tjolomadoe has met the criteria as a heritage tourist attraction with the highest aspect of history.